2009
DOI: 10.1021/ol802740b
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Orthogonality of S-Benzoxazolyl and S-Thiazolinyl Glycosides: Application to Expeditious Oligosaccharide Assembly

Abstract: Thorough mechanistic studies of the alkylation pathway for the activation of glycosyl thioimidates have led to the development of the “thioimidate-only orthogonal strategy”. Discrimination amongst S-thiazolinyl (STaz) and S-benzoxazolyl (SBox) anomeric leaving group was achieved by fine-tuning of the activation conditions. Preferential glycosidation of a certain thioimidate is not simply determined by the strength of activating reagents; instead, the type of activation – direct vs. indirect – comes to the fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
50
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 24 publications
2
50
0
Order By: Relevance
“…24–27 Yet this strategy remains somewhat under-developed with too few known examples to become universally applicable. Only the following examples are known to date: the original S -phenyl vs fluoride introduced by Kanie et al, 24,25,28 thioimidate-based approaches developed in our lab, 19,2931 Hotha’s O -pentenyl vs O -propargyl, 32 and O -allylphenyl-based approach also introduced by our group. 33 Likewise, we reported a related, albeit less flexible, semiorthogonal approach using S -ethyl vs O -pentenyl, 34 which was extended to fluoride vs O -pentenyl by Fraser-Reid and Lopez.…”
Section: Resultsmentioning
confidence: 99%
“…24–27 Yet this strategy remains somewhat under-developed with too few known examples to become universally applicable. Only the following examples are known to date: the original S -phenyl vs fluoride introduced by Kanie et al, 24,25,28 thioimidate-based approaches developed in our lab, 19,2931 Hotha’s O -pentenyl vs O -propargyl, 32 and O -allylphenyl-based approach also introduced by our group. 33 Likewise, we reported a related, albeit less flexible, semiorthogonal approach using S -ethyl vs O -pentenyl, 34 which was extended to fluoride vs O -pentenyl by Fraser-Reid and Lopez.…”
Section: Resultsmentioning
confidence: 99%
“…It was also reported that the SBaz leaving group can be very rapidly activated for glycosylation in the presence of AgBF 4 and is applicable to selective activation over other types of leaving groups involving S -alkyl and O -pentenyl glycosides [55]. It was also observed that the SBaz leaving group can be activated in the presence of MeOTf, but not in the presence of weaker alkylating reagents, which created a basis for selective activation of STaz donors with benzyl bromide or methyl iodide in the presence of glycosyl acceptors equipped with SBaz anomeric group [35]. …”
Section: S-benzothiazolyl Derivativesmentioning
confidence: 99%
“…SBox glycosides also showed promising orthogonal combinations with glycosyl alkoxyimidates [64] and STaz glycosides [35]. The orthogonality with other thioimidates is a unique feature of this methodology because conventional orthogonal activation [65, 66] requires two different classes of leaving groups, whereas here both leaving groups are of the same class.…”
Section: S-benzoxazolyl Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously shown in our laboratory, S -thiazolinyl donors are activated via the remote nitrogen. 17 In strong contrast, bicyclic leaving groups SBox or OBox are activated via the anomeric sulfur or oxygen atom, respectively (Fig. 1).…”
mentioning
confidence: 99%